MITOS TEMBANG DURMA KUNTILANAK PADA FILM KUNTILANAK - Elara Karla N. (Institut Seni Indonesia Surakarta, 2014)
The article is the result of a research about mythos of a song Durma Kuntilanak in the film Kuntilanak byRizal Mantovani. Problem in the article is how film Kuntilanak describes about mythos of tembang DurmaKuntilanak. The research aims to learn the reality of film Kuntilanak that represents the song Durma Kuntilanakas a mythos created by the film maker. To analyze the sign and meaning in order to find understanding anddescription of the mythos in the story of film Kuntilanak, the research uses the semiotics approach ofChristian Metz. Metz said that the cinematographic indicator and sign have a â€œmotivationâ€ and â€œreasonableâ€relationship. It means that indicator and sign in cinematographic will always be diegesis with the referrednature (story). The paradigm will be applied in narrative structure of film Kuntilanak that has been divided intothree sessions and then classified to be sequences covering â€œcause-effectâ€. The result shows that themethod of storytelling in film Kuntilanak uses narrative conventional structure and â€œcause-effectâ€ sceneswhen the song Durma Kuntilanak is presented by the repeated pattern. It makes the audience leaded to theunderstanding of story in accordance to â€œits pathâ€ and believed the mythos of song Durma Kuntilanak bystressing the â€œcause-effectâ€ scene. Even though the â€œcause-effectâ€ scene is presented by using symbolicpictures, the connotative signs in the symbolic pictures are no more arbitrary because of the narrativestructure used in the film. As if the audience is leaded to understand easily the meaning of story in accordanceto the presented pictures. The connotative sign can be no more given a meaning deliberately.Keywords: mythos of song Durma Kuntilanak, narrative conventional structure, semiotics of film Christian Metz